Total and temporal patterning of physical activity in adolescents and associations with mental wellbeing - Abdulwahab D. Alshallal; Olivia Alliott; Soren Brage; Esther M. F. van Sluijs; Paul Wilkinson; Kirsten Corder; Eleanor M. Winpenny (BMC, 2024)
Abstract Background There is limited understanding of the extent to which differences in physical activity across the day and week may be associated with mental wellbeing. Such an understanding is needed for better targeting of interventions. In this study, we describe total and temporal patterning of physical activity across the week in adolescents (age 13-14y) and assess their prospective associations with mental wellbeing. Methods 1,983 13-14-year-old adolescent participants based in Cambridgeshire and Essex, recruited between 2016 and 2017 into the Get Others Active Trial provided data at baseline and 4 months. Physical activity was measured at baseline using wrist-worn accelerometers across different time segments (whole week, weekday schooltime, weekday out of school, and weekend), and operationalized as average movement-related acceleration for each time segment. Mental Wellbeing at baseline and 4 months was measured using the Warwick Edinburgh MentalWellbeing Scale. Associations between physical activity across different time segments (whole week, weekday schooltime, weekday out of school, and weekend) and mental wellbeing at 4 months were investigated using sex-stratified multi-level regression models, adjusted for covariates, and both adjusted and unadjusted for baseline mental wellbeing. Results Our analyses found positive associations between physical activity and mental wellbeing at 4 months, unadjusted for baseline wellbeing. Among girls, positive associations were shown when considering physical activity across the whole week 0.07 (95% CI, 0.03-0.12), and across all separate time periods studied: weekday schooltime 0.07 (95% CI, 0.02-0.11), weekday out-of-school time 0.07 (95% CI, 0.03-0.12), and weekend 0.07 (95% CI, 0.02-0.11). For boys, similar associations were observed for activity across the week 0.07 (95% CI, 0.03-0.11), during weekday schooltime 0.08 (95% CI, 0.04-0.12), and weekday out-of-school time 0.07 (95% CI, 0.03-0.11), but not the weekend 0.01 (95% CI, -0.03-0.05). For both girls and boys, associations were attenuated below significance after adjusting for baseline wellbeing. Conclusions This longitudinal analysis showed positive associations between physical activity and later mental wellbeing in both male and female adolescents across most time segments. Higher physical activity throughout the week may be associated with better mental wellbeing in the adolescent population. Further research is required to understand determinants of change in wellbeing over time. Trial Registration Registration Number: ISRCTN31583496. Registered: 18/02/2014.